Placental pathologic features in obesity - Beneventi, Fausta; Bellingeri, Camilla; De Maggio, Irene; Cavagnoli, Chiara; Fumanelli, Silvia; Ligari, Elisa; Fiandrino, Giacomo; Cesari, Stefania; Spinillo, Arsenio (Placenta (Eastbourne), 2023)
Obesity in pregnancy is associated with adverse long-term consequences both in the mother and in offspring. Maternal obesity induces a metabolic-inflammatory state that could impact on placental function and could mediate the adverse outcomes. The purpose of this study was to compare the major placental histological characteristics of non-diabetic obese women to lean controls, focusing on uncomplicated pregnancies. Prospective case-control study comparing placental histopathological features between 122 non-diabetic obese women and 185 non-obese controls. The analysis was performed on overall subjects, then uncomplicated pregnancies from both groups were analyzed. Placenta pathologic findings were recorded according to standard classification. Both in overall analysis and among the subset of subjects with an uncomplicated pregnancy, obese subjects had higher risks of maternal vascular malperfusion (MVM) (respectively OR=2.2, 95%CI =1.3–3.7 and OR=4.2, 95%CI=2.1–8.5), fetal vascular malperfusion (FVM) (respectively OR=6.3, 95%CI=3.1–12.5 and OR=7.2, 95%CI=3–17.2), maternal and fetal inflammatory response placental lesions and villitis (VUE) (respectively OR=2.5, 95%CI=1.1–5.6 and OR=10.8, 95%CI=3.3–35.3) compared to controls. Among uncomplicated pregnancies and after adjustment for confounders, first trimester BMI was significantly associated with overall MVM, overall FVM, maternal inflammatory, fetal inflammatory response and VUE. Placentas from obese women showed a significantly higher risk of maternal and fetal vascular and inflammatory placental lesions, both in overall population and in the subgroup with uncomplicated pregnancies. The metabolic and inflammatory dysfunctions typical of obesity could have an impact on placental development and function, which could be a mediator of the detrimental effects of obesity on pregnancy outcome and on future health of the offspring. •Obese women have higher risk of placental maternal and fetal vascular malperfusion.•Obese women have higher risk of placental acute and chronic inflammation.•Placentation differs significantly between obese and non-obese women.•Placenta could mediate the effects of obesity on pregnancy and on the offspring.